Crafting in the World Materiality in the Making - Burke, Clare; Spencer-Wood, Suzanne M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume expands understandings of crafting practices, which in the past was the major relational interaction between the social agency of materials, technology, and people, in co-creating an emergent ever-changing world. The chapters discuss different ways that crafting in the present is useful in understanding crafting experiences and methods in the past, including experiments to reproduce ancient excavated objects, historical accounts of crafting methods and experiences, craft revivals, and teaching historical crafts at museums and schools. Crafting in the World is unique in the diversity of its theoretical and multidisciplinary approaches to researching crafting, not just as a set of techniques for producing functional objects, but as social practices and technical choices embodying cultural ideas, knowledge, and multiple interwoven social networks. Crafting expresses and constitutes mental schemas, identities, ideologies, and cultures. The multiple meanings and significances of crafting are explored from a great variety of disciplinary perspectives, including anthropology, archaeology, sociology, education, psychology, women's studies, and ethnic studies. This book provides a deep temporal range and a global geographical scope, with case studies ranging from Europe, Africa, and Asia to the Americas and a global internet website for selling home crafted items.
Introduction -- Section I: Reconstructing ancient craft practice through archaeology and experiment -- Ch 1. Made to Remake the World: Bronze-Age Tools and the idea of Craft -- Ch 2. Looking over the shoulder of the Bronze Age metalsmith: Using wear analysis to understand metalsmithing practices -- Ch 3. Grasping at Threads - a Discussion on Archaeology and the Study of Craft -- Section II: Reconceptualizing Crafting -- Ch 4. Crafting History: How the World is Made. The case of Islamic archaeology -- Ch 5. Crafting a progressive nostalgia: radical embroidery as a negotiation of the past into a positive future -- Ch 6. Beauty and Grace in making Artifacts: An Anthropological Gaze upon Crafting in the World -- Section III: Teaching and Experiencing Crafts -- Ch 7. The Temporal and Spatial Diffusion of the Sloyd Educational Crafting Tradition Across the Landscape of Western Culture -- Ch 8. Hold Infinity in the Palm of Your Hand: learning the world through place-based craft -- Ch 9. Crafts and Living History: Old Sturbridge Village -- Section IV: The Meanings of Crafting in Modern Societies -- Ch 10. Hands to the Potter's Wheel: A case of technological change in pottery production in Pomaire, Chile -- Ch 11. "El Proyecto Paraguas" (The Umbrella Project): Craft knowledge as tactical tool in marginalized communities in Argentina -- Ch 12. Etsy as a global community of practice? -- Ch 13. Commentary/conclusion.
Keywords: Archaeology; Cultural property; Archaeology; Cultural Heritage